Comparative Evaluation on the Effect of Zinc-Probiotic and Zinc Therapy in Pediatric Acute Gastroenteritis - Azim, Md Anwarul; Doza, Badrud; Iqbal, Shahed; Chowdhury, Farah; Biswas, Sanjoy Kanti (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Acute watery diarrhea in under 5 children is still a major healthburden worldwide despite all available efforts that have been made to reduce itsincidence and prevalence. Mortality rate is still high among under 5 children.Therefore, appropriate and comprehensive management of diarrhea is essential.There are lot of studies on the role of zinc and probiotic in reducing the duration andseverity of acute watery diarrhea. This study emphasized on compared effect ofusing a combination zinc –probiotic and zinc in pediatric acute gastroenteritis. Materials and methods: This was a randomized controlled trial type study,conducted at Department of Pediatric Gastroenterology at Chattogram Maa-OShishuHospital Medical College from November 2018 to March 2019. A total of 100numbers of children ages 3 months to 5 years with acute watery diarrhea wereenrolled those who were fulfilled the selection criteria. They were divided into twogroups. Group A (n=50) received zinc-probiotics combination therapy and group B(n=50) received zinc only. Measurement of disease severity was based on thefrequency of diarrhea (Times/day) and duration of diarrhea (Hours) after initial drugconsumption. Results: Among the study population 63.5% male & 32.7% female in group A and56.4% male & 34.5% female in group B. Duration of acute watery diarrhea wassignificantly reduced in group A than group B (56.4 hours versus 70.80 hoursrespectively). We also observed significant difference in length of hospital stay inGroup A and Group B (68.16 hours vs 83.04 hours) respectively. Conclusion: Combination therapy was more effective in reducing the severity ofacute watery diarrhea than zinc alone therapy in under 5 children. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 74-77